2012
DOI: 10.1007/978-3-642-31680-7_15
|View full text |Cite
|
Sign up to set email alerts
|

Risk Communication Design: Video vs. Text

Abstract: Abstract. There are significant differences between older and younger adults in terms of risk perception and risk behaviors offline. The previously unexplored existence of this dissimilitude online is the motivation for our work. What are the risk perceptions of older adults? How are these correlated with the classic dimensions of risk perception offline? Can we leverage episodic memory, particularly relevant for older adults, to increase the efficacy of risk communication? We conduct a survey based experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…For example, both Garg et al and Blythe et al show that due to varying perceptions and abilities that correlate with demographic factors, computer-based risk communication should employ some degree of demographic targeting [19], [5]. While this work is likely applicable to wearable computing risk communication, we believe that a better understanding of users' information risk acceptance in this domain is warranted prior to examining risk communication.…”
Section: Related Workmentioning
confidence: 90%
“…For example, both Garg et al and Blythe et al show that due to varying perceptions and abilities that correlate with demographic factors, computer-based risk communication should employ some degree of demographic targeting [19], [5]. While this work is likely applicable to wearable computing risk communication, we believe that a better understanding of users' information risk acceptance in this domain is warranted prior to examining risk communication.…”
Section: Related Workmentioning
confidence: 90%
“…Web-based studies: We found only three web-based studies. One is a survey-based experiment [66] conducted online with older adults and a second is a small online study with five participants [173]. A third study [44] does not evaluate the educational tool itself but instead uses the tool to collect consumer behaviour data online.…”
Section: Types Of Evaluationmentioning
confidence: 99%
“…Alternatively, it might be possible that an audio-visual video is more likely to be retained compared to a single visual text with a pictograph. Hence, providing the same risk information as a short video might lead to an increase in risk perception (Conijn et al, 2020 ; Garg, Camp, Connelly, & Lorenzen-Huber, 2012 ). Remarkably, participants evaluated the personalised risk message positively, although it did not achieve the intended effect on risk perception.…”
Section: Discussionmentioning
confidence: 99%